2020
DOI: 10.1061/(asce)mt.1943-5533.0003270
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Hydromechanical Performances of a Stabilized Compacted Soil Exposed to Successive Wetting–Drying Cycles

Abstract: This study intends to examine the impact of successive wetting and drying cycles on the strength and the hydraulic conductivity of lime and cement treated soil, with a special emphasis on the protocol that is employed to impose the cycles. Compacted specimens were cured for 90 days before being exposed to different numbers of wetting and drying cycles. These cycles were imposed to treated samples with two protocols. The first one is based on oven drying and full saturation, while the second one is based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Nevertheless, it was also reported that wetting-drying cycles would resulted in a breakage or softening of the bonds of cementitious compounds, leading to a decrease of soil strength (Rao et al, 2001;Guney et al, 2007;Stoltz et al, 2014;Rosone et al, 2018;Cuisinier et al, 2020).…”
Section: Wetting Fluid Effect On the Gmax During Wetting-drying Cyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it was also reported that wetting-drying cycles would resulted in a breakage or softening of the bonds of cementitious compounds, leading to a decrease of soil strength (Rao et al, 2001;Guney et al, 2007;Stoltz et al, 2014;Rosone et al, 2018;Cuisinier et al, 2020).…”
Section: Wetting Fluid Effect On the Gmax During Wetting-drying Cyclesmentioning
confidence: 99%
“…Even though the soil properties were improved by lime treatment, the long-term durability of lime-treated soils might be altered when the soils were exposed to cyclic climate loadings such as wetting-drying cycles. Several studies revealed that the imposition of wetting-drying cycles on lime-treated soil would partially destroy the cementitious bonds and alter the soil microstructure, leading to progressive loss of soil strength (Aldaood et al, 2014;Stoltz et al, 2014;Cuisinier et al, 2020;Nabil et al, 2020), and an increase in compressibility and hydraulic conductivity (Rosone et al, 2016(Rosone et al, , 2018Cuisinier et al, 2020). Nevertheless, Anggraini et al (2016) indicated that wetting-drying cycles could make the curing time longer, and therefore the durability of stabilized soils was enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…This may have led to shrinkage cracks during the drying cycle resulting in a compromised microstructure of the OPC stabilized soil. Cuisinier et al [31] state that some investigations have revealed that imposition of the first cycle of wetting and drying could induce a significant change in the microstructure of the soil. As a result, the strength of OPC stabilized soil decreases after the first cycle of wetting and drying.…”
Section: Ucs (Kpa)mentioning
confidence: 99%
“…They indicated that an intensive cyclic wetting-drying induces micro-cracks resulting in a decrease in the small shear strain modulus, associated to a decrease of the mechanical performances. Cuisinier et al [22] also showed the harmful effects on strength and hydraulic conductivity of wetting and drying cycles on cement treated soil performances. Despite this information on the influence of climatic conditions and cyclic variations of water content on the hydro mechanical performances of treated soils, knowledge on their effect on the thermal properties of soil is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…In the long term, fluctuations of the cable temperature will induce successive drying/wetting cycles of the soil surrounding the cable. It is well known that successive wetting and drying can alter the characteristics of treated soils [19,20], this alteration being associated to a progressive modification of the treated soil microstructure. Tang et al [21] studied the cyclic wetting/drying effects of the stiffness of a lime-treated clayey soil by using bender elements.…”
Section: Introductionmentioning
confidence: 99%